Analysis of the internal electric fields of pristine ice crystals and aggregate snowflakes, and their effect on scattering. (June 2019) - McCusker, K.; Westbrook, C.D.; Moiola, A.
Highlights: The internal field complexity of monocrystals increases with size parameter. The field within a plate comprises a "distorted" plane wave and a standing wave. The field within complex aggregates shows little variation with size parameter. Individual monomers comprising aggregates act independently of each other. Different field components are important for scattering in different directions. Abstract: The discrete dipole approximation is used to explore the internal electric fields of plane-wave-illuminated ice particles, and analyse their differential scattering cross sections. The results are displayed for monocrystals and aggregates of size parameters x = 2 and x = 10 . We show that the field is relatively uniform for x = 2, but for monocrystals of x = 10 there is a complex internal structure. For a hexagonal plate, this structure is a combination of two components: a "distorted" plane wave, with wavefronts aligned perpendicular to the incident wave close to the centre of the plate, and curved forward near the particle boundary; and a standing wave, internally reflected around the perimeter. The former is due to the transverse component of the field i.e., the component perpendicular to the incident wave, and the latter is due to the component parallel to the incident direction. Focussing of the field towards the forward side of the particle is observed. As the particle complexity is increased due to aggregation, the field becomes smoother and less focussing is seen. For complex aggregates, the individual monomers act independently of one another, suggesting simplified methods of calculating scattering from such particles. The influence of the internal fields on far-field scattering is explored. It is demonstrated that scattering in the forward and backward directions is dominated by the transverse component. The parallel component contributes to sidescattering, with its influence on total scattering decreasing with particle complexity. We propose that this is due to the inability of complex particles to maintain a standing wave, diminishing much of the sidescattering observed for monocrystals. Comparisons of the far-field scattering properties of complex aggregates using the discrete dipole and Rayleigh–Gans approximations are also presented for x = 2 and x = 10, along with results obtained using a soft sphere approximation.